Synthesis and Antimicrobial Properties of Friedel-Crafts Polyketones - Patel, B.V.; Patel, B.T.; Patel, R.M. (Asian Journal of Chemistry, 2010)
The low molecular weight polyketones were prepared by Friedel-Craftsreaction from phenetole, chloroacetyl chloride (CAC), 1,2-dichloroethane(DCE) and dichloromethane (DCM) using anhydrous aluminium chlorideas catalyst and carbon disulphide as a solvent. The polyketones thusobtained were characterized by % chlorine content, IR spectroscopy,vapour pressure osmometry, thermogravimetry and differential scanningcalorimetry. All these resins were tested for their biological activity againstbacteria and fungi. The results indicate that the growth of the testedorganisms was inhibited by the polyketones to a considerable extent.